2015
DOI: 10.1016/j.healthpol.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Policy and planning of prevention in Italy: Results from an appraisal of prevention plans developed by Regions for the period 2010–2012

Abstract: Health policies on disease prevention differ widely between countries. Studies suggest that different countries have much to learn from each other and that significant health gains could be achieved if all countries followed best practice. This paper describes the policy development and planning process relating to prevention activities in Italy, through a critical appraisal of Regional Prevention Plans (RPPs) drafted for the period 2010-2012. The analysis was performed using a specific evaluation tool develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Second, the monitoring of regions' and hospitals' healthcare performance has highlighted a wide gap not only between regions but also between hospitals operating in the same region, both of which are closely linked to weak administrative and management capacities [9,11,13,[15][16][17]. Third, a three-year programme does not demonstrate a longterm view, evidencing the lack of strategic oversight and planning across the health system [9,17,21]. Given these considerations, it is clear that the healthcare system would benefit from a re-organization that pays greater attention to long-term strategic reforms.…”
Section: The Expected Outcomes and Potential Limitations Of The Reformmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the monitoring of regions' and hospitals' healthcare performance has highlighted a wide gap not only between regions but also between hospitals operating in the same region, both of which are closely linked to weak administrative and management capacities [9,11,13,[15][16][17]. Third, a three-year programme does not demonstrate a longterm view, evidencing the lack of strategic oversight and planning across the health system [9,17,21]. Given these considerations, it is clear that the healthcare system would benefit from a re-organization that pays greater attention to long-term strategic reforms.…”
Section: The Expected Outcomes and Potential Limitations Of The Reformmentioning
confidence: 99%
“…This decline suggests that RRPs are effective tools for improving economic and financial performance in the short term [9,13,16,[18][19][20] with some limitations. Indeed, several authors have observed i) RRPs' limited efficacy in solving the structural causes of the deficits and ii) the lower quality of health prevention projects developed in Italian regions with financial deficits and recovery plans [9,16,21].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, a strong concern of the heterogeneity in the distribution of vaccination coverage is observed from country to country [43] and, in Italy, even from region to region. In a recent review of the vaccination regional plans (RPPs), Rosso et al (2015) showed how such variability is not only in the outcomes, but also in the appraisal activity of regional plans, and the initiatives against unequal access to vaccine immunization are still far from an effective implementation [44].…”
Section: Discussionmentioning
confidence: 99%
“…A study [19] that performed a critical appraisal of the RPPs 2010–2012, found that geographical differences in the quality of the RPPs and the opportunity of assessing the planning process may strengthen public health capacity for prevention. According to our experience, the CoP was felt by RPs as an opportunity for the Regions with less capacity in prevention planning processes to gain experience from others more skilled, even if gaps still exist.…”
Section: Discussionmentioning
confidence: 99%
“…According to our experience, the CoP was felt by RPs as an opportunity for the Regions with less capacity in prevention planning processes to gain experience from others more skilled, even if gaps still exist. In the future, to set up the next RPPs, it will be advisable to have a national follow-up of some critical steps of the regional planning process to avoid, for example, a lack of consideration of the principles of evidence-based prevention and to effectively tackle health inequalities [19, 20], as well as to retrieve the utmost from the national health behavioural surveillance systems well established in Italy [21] in order to monitor inequalities and outcome progress in prevention.…”
Section: Discussionmentioning
confidence: 99%